High-calcium milk improves osteoporosis in postmenopausal women by regulating intestinal flora and steroid hormone biosynthesis - Zhao, Yanyan; Li, Xianping; Liu, Yanpin; Wang, Qishan; Zhao, Junying; Pan, Hang; Chen, Huo; Liu, Bin; Qiao, Weicang; Lin, Li; Jin, Yue; Chen, Lijun (Frontiers in Nutrition, 2025)
BackgroundPostmenopausal calcium loss increases osteoporosis risk in middle-aged and older women. While dairy products are a known calcium source that supports bone health, limited research addresses their specific effects on osteoporosis prevention in this population.MethodsA one-year randomized controlled trial recruited 97 postmenopausal women, randomly assigned to a high-calcium milk group (HCM, 51), consuming 400 mL nutrient-enriched fresh milk daily, or a control milk group (CM, 46), consuming 400 mL of regular fresh milk.ResultsA one-year randomized controlled trial showed that the high-calcium milk group significantly increased lumbar spine bone mineral density (L1-4 BMD), slowed bone loss in the left hip and femoral neck, elevated serum phosphorus and 25-hydroxyvitamin D levels, and modulated the bone formation marker procollagen type I N-terminal propeptide compared with the regular milk group at 6 months. 16S ribosomal ribonucleic acid sequencing showed that high-calcium milk significantly altered the β-diversity of the intestinal flora, increasing the abundance of beneficial bacteria such as Bacteroides, Oscillibacter, and Subdoligranulum, while decreasing the abundance of Firmicutes and Weissella at 12 months. Metabolomics analysis revealed that high-calcium milk improved bone quality by modulating steroid hormone biosynthesis and arachidonic acid metabolic pathways, and that L1–4 BMD was positively correlated with Faecalibacterium spp. and adenine nucleotide.ConclusionsOur study suggests that high-calcium milk can effectively delay postmenopausal osteoporosis by regulating intestinal flora and metabolic pathways, providing a new target for osteoporosis intervention.Clinical trial registry numberChiCTR2200064825 (https://www.chictr.org.cn/bin/home).